Potential of bioactive compounds in Indonesian endemic Nutmeg (Myristica fragrans and Myristica argentea) and their applications in health: An overview - Azrial, Fahmi (Journal of Evidence-based Nursing and Public Health, 2025)
Background: Nutmeg (Myristica fragrans and Myristica argentea), an Indonesian endemic plant from the Maluku Islands, has long been used in traditional medicine to treat digestive disorders, joint pain, and infections. While Myristica fragrans has been widely studied, research on M. argentea remains limited, despite both species containing bioactive compounds such as phenylpropanoids (e.g., myristicin), terpenoids, and flavonoids, which exhibit antioxidant, antimicrobial, and anti-inflammatory properties. Key challenges include optimizing eco-friendly extraction methods and exploring untapped therapeutic potential. This review consolidates the latest scientific evidence on nutmeg’s bioactive compounds and their health benefits, including anticancer, antidiabetic, and neuroprotective effects, as well as their prospects for sustainable therapeutic development. Methods: The study was conducted by searching PubMed, Scopus, and Google Scholar using keywords related to nutmeg’s bioactive compounds and medicinal properties. Findings: Findings reveal that both M. fragrans and M. argentea possess significant antidiabetic, antioxidant, anticancer, anti-inflammatory, and neuroprotective activities. Extraction methods range from conventional techniques like hydrodistillation and organic solvents to modern approaches such as Supercritical Fluid Extraction (SFE) and Ultrasound-Assisted Extraction (UAE). Additionally, nutmeg shows promise as an antimicrobial and cardioprotective agent, though its psychoactive compounds warrant caution. Conclusion: Potential applications include nutraceuticals, cosmetics, and pharmaceuticals, with waste utilization enhancing sustainability. Novelty/Originality of this article: The novelty of this review lies in its comprehensive comparison of both nutmeg species, emphasis on sustainable extraction techniques, and exploration of understudied therapeutic potentials, offering new insights for future research and industrial applications.